Creation and evaluation of a cancer survivorship curriculum for pediatric resident physicians - Schwartz, Lindsay F.; Braddock, Clarence H.; Kao, Roy L.; Sim, Myung-Shin; Casillas, Jacqueline N. (Journal of cancer survivorship, 2018)
Purpose There is a paucity of formal clinician education concerning cancer survivorship care, which produces care barriers and poorer outcomes for survivors of childhood cancer. To address this, we implemented a curriculum in childhood cancer survivorship care for pediatric residents at the University of California, Los Angeles (UCLA). We examined the efficacy of this curriculum following program completion. Methods A case-based curriculum was created and integrated within existing educational structures using Kern’s model. We utilized the retrospective pre-posttest method to evaluate participating residents’ knowledge, clinical skills, and attitudes towards cancer survivorship topics before and after receiving the curriculum. Pre-posttest items were compared using paired t tests and one-sided binomial tests. We analyzed free-response question items for major themes using constant comparative methods. Results Thirty-four residents completed the curriculum and its evaluation. Each assessment item significantly increased from pre- to post-curriculum; p < 0.05. Greater than 40% of residents improved in all but one assessment item post-curriculum; p < 0.05. Residents reported the curriculum enhanced their pediatric knowledge base ( M = 3.24; SD = 0.65) and would recommend it to other residency programs; M = 3.24; SD = 0.69. Major themes included residents’ request for additional oncofertility information, training in counseling survivors, and cancer survivorship training opportunities. Conclusions A cancer survivorship curriculum can successfully increase trainees’ knowledge, clinical skills, and comfort in discussing topics relevant to survivorship care. Implications for Cancer Survivors With increasing numbers of childhood cancer survivors living into adulthood, residents will likely treat this population regardless of intended career path. This curriculum represents one method to deliver formal cancer survivorship training.